THE USE OF BAGASSE SYNTHETIC SURFACTANTS AS MATERIAL FOR ENVIRONMENTALLY FRIENDLY POLICIES TO IMPLEMENT ENVIRONMENTAL MANAGEMENT - Rini Setiati; Paulus Suryono Adisoemarta; Muhammad Taufiq Fathaddin; Tarida Surya Marpaung; Astri Rinanti; Jachanan Satriabudi (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
Aims: The aim of this research study is to show that the use of synthetic surfactant from bagasse is Environmentally Friendly Policies. Environmental management is an important step that needs to be taken on this immediate moment. Various human and industrial activities surely have affected the environment. Environmental management should include a number of groups from different varieties such as academics, policy makers, non-governmental organizations, corporations’ employees, government’s employees and related multidisciplinary groups. Methodology and Results: Environmental management will produce an ecological process and shapes industrial ecology which consists of four components namely; production, consumption, waste/by-products and raw materials. Bagasse as one of industrial solid wastes involved in environmental management will also produce ecological process. Bagasse which is produced from sugarcane processing can be further reprocessed into SLS surfactant that is useful for oil companies as injection fluid on reservoirs to improve oil recovery level. Conclusion, significance and impact of study: Environmental management can be applied between two industries that have mutualism symbiosis relationship through secondary production. Waste minimization can be achieved through bagasse processing. Sugarcane bagasse reprocessing into SLS surfactant is a sustainable program that supports sustainable material management effort. The action to reprocess natural waste into a valuable economical material can also alter human behavior into a more environmental friendly type of behavior.